Strength and microstructural properties of fly ash based geopolymer concrete containing high-calcium and water-absorptive aggregate - Embong, R. (Elsevier Ltd, 2016)
In this research, performance of limestone and oil palm shell (OPS) as the alternative aggregates in fly ash based geopolymer concrete was evaluated based on the fresh and hardened concrete test. Fly ash and oil palm shell were studied due to their abundant availability as industrial and agricultural waste. Experimental works were conducted by replacing the portion of coarse and fine aggregate in concrete with limestone and oil palm shell in various percentages. Evaluation of its performance was done based on slump, compressive strength, and porosity test. Microstructure analysis was added via Scanning Electron Microscope (SEM) and Energy Dispersive X-Ray (EDX) test to support the generated hypothesis. From the fresh properties test, the increasing amount of limestone and OPS have shortened the setting time of fresh geopolymer concrete, even though they presented small variations in the slump's height and diameter results. The availability of Calcium Aluminate Silicate Hydrate (C-A-S-H) structure in limestone based specimen and higher polycondensation rate due to optimum water content in OPS based specimens have stimulated the rapid production of geopolymer gel and improved the strength performance of geopolymer concrete in ambient curing condition. Moderate water absorption from OPS fibers and additional dissolution of Al and Si elements due to formation of C-A-S-H gels from limestone inclusion have presented 10 OPS and 25 limestone as the optimum replacement to river sand and coarse granite aggregate, respectively. In ambient curing, 25 limestone presented a 35.23 higher strength while 10 OPS had 11.01 higher strength than control. An escalation to the curing temperature reduced the efficiency of both aggregates, where only 25 limestone was able to produce specimen with 2.34 higher strength than control A supportive analysis from SEM and EDX has also revealed the existence of poly(sialate), poly(sialate-siloxo), poly(sialate-disiloxo) and sialate link in the geopolymer matrix. From this research, the applications of limestone and oil palm shell in geopolymer concrete have presented a nurturing result, particularly as the alternative aggregates in ambient-cured application. Â© 2015 Elsevier Ltd. All rights reserved.